2022
DOI: 10.3390/diagnostics12122993
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Agreement When Agreement Is Hard to Assess—The Agatston Score for Coronary Calcification

Abstract: Method comparison studies comprised simple scatterplots of paired measurements, a 45-degree line as benchmark, and correlation coefficients up to the advent of Bland–Altman analysis in the 1980s. The Agatston score for coronary calcification is based on computed tomography of the heart, and it originated in 1990. A peculiarity of the Agatston score is the often-observed skewed distribution in screening populations. As the Agatston score has manifested itself in preventive cardiology, it is of interest to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 100 publications
(199 reference statements)
0
3
0
Order By: Relevance
“…Since its original proposal back in 1990 [30], the CAC score has repeatedly been subject to agreement assessments in order to investigate the score's reliability. A recent review [31] found sample sizes to be highly variable in studies of agreement on the CAC score , and research groups focused on intra-and inter-rater as well as intra-and inter-scanner variability assessments. Andersen and Gerke [31] concluded that only very few research articles were capable of deriving limits of agreement that fit the observed data visually in a convincing way.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Since its original proposal back in 1990 [30], the CAC score has repeatedly been subject to agreement assessments in order to investigate the score's reliability. A recent review [31] found sample sizes to be highly variable in studies of agreement on the CAC score , and research groups focused on intra-and inter-rater as well as intra-and inter-scanner variability assessments. Andersen and Gerke [31] concluded that only very few research articles were capable of deriving limits of agreement that fit the observed data visually in a convincing way.…”
Section: Datamentioning
confidence: 99%
“…A recent review [31] found sample sizes to be highly variable in studies of agreement on the CAC score , and research groups focused on intra-and inter-rater as well as intra-and inter-scanner variability assessments. Andersen and Gerke [31] concluded that only very few research articles were capable of deriving limits of agreement that fit the observed data visually in a convincing way. This is why alternative methods like fractional polynomial modeling may prove useful in assessing the agreement of the CAC score.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation